PERSEPSI PENGGUNAAN MOBILE BANKING TERHADAP KEMUDAHAN DALAM BERTRANSAKSI - Lestari, Indriati Ayu; Umilah, Lia (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine the perpection of the use of Mobile banking on the ease of transactions. The method used is qualitative descriptive method with a Technology Acceptence Model (TAM) approach. The data collection in this study used a questionnaire users who had been selected as samples. This reseacrh was conducted based on several indicators including to determine the perception of use, benefits and ease of use Mobile banking in transactions, interest in transaction using Mobile banking and perceptions of risk in the use of mobile banking. The result reveal that in the perception of use, many respondents know and use Mobile banking applications in transactions, and can provide benefits, convenience, and risk that occur.